The ways of the small business development in the context of the political and financial instability in Ukraine - Shyshkin, Viktor (Management and Entrepreneurship: Trends of Development, 2017)
Recently the small-scale enterprises’ activity attracts the attention of the researchers, economists and politicians all over the world. This fact is related to producing the considerable portion of the GDP, solving the employment problems and the competitiveness increasing of the national economy by the small-scale enterprises. In this connection, the significant contribution of the small-scale enterprises to the high market performance creating and the various sectors of the national economy competitiveness improving stipulate the article subject relevance. Also the article topicality is due to the fact that today the small business in the need of the government support. Purpose. The subject of the study is the theoretical, methodological, statistical and practical aspects of the ways of the small business development search in the context of the unstable situation in the country. The purpose of the paper is to determine the necessary measures in the small business development field with the aim of leveling the negative internal and external factors. Design/methodology/approach. The basic principles of this research are the causality and objectivity principles, systematic and comparative methods, institutional and structural-functional approach. Findings. In this article the elaboration and implementation of the effective package plan is suggested. The purpose of such plan is to develop the small business in Ukraine on the integrity and system basis. It should include the following measures: The development and implementation of the government support mechanism. It should consist in the realization of the development programs and business support and should be adopted on the national and regional levels. The elaboration and legislative assignment of the legal control mechanism for the small-scale enterprises’ activity. The elaboration and application of the government influence mechanism on the small business formation and development processes. This measure aims to create favorable economic conditions. The development of the effective export mechanism for the small-scale enterprises. The improving of the investment climate in the country. Research limitations/implications. The scientific significance of the article consists in the research of the possible ways of the small business development, taking into account the features of the market environment in Ukraine. Originality/value. The suggested in this article measures will further the increase of the Ukrainian economy competitiveness and will accelerate the process of Ukrainian integration in the world economy. The small business in Ukraine will be able to develop, operate on the appropriate level and overcome a lot of the negative financial and political factors by virtue of the government support